Corrected Intraocular Pressure Variability with Central Corneal Thickness Measurement - Ahmed, Mohamed Attia Ali (Clin Ophthalmol, 2020)
PURPOSE: To evaluate variability in measured intraocular pressure (IOP) values when correlated with central corneal thickness measurements obtained by both ultrasonic and optical tools. PATIENTS AND METHODS: We included 46 eyes of 46 healthy subjects (age range 35–76 years). Exclusion criteria for the current study were patients with confirmed diagnosis of glaucoma, glaucoma suspect patients and those having corneal opacities, scars or prior cornea-based laser vision correction. Central corneal thickness (CCT) was measured using two methods: ultrasonically (CCT1) by pachymeter and optically (CCT2) using anterior-segment optical coherence tomography (AS-OCT). The IOP was measured in all subjects using Goldmann applanation tonometry (GAT). RESULTS: No significant difference was detected comparing intraocular pressure values and CCT-corrected intraocular pressure (IOPcc1 and IOPcc2) (P=0.47 and P=0.06, respectively) among the study participants. A significant negative correlation was found between corneal thickness-corrected IOP values and the measured central corneal thickness by both optical and ultrasonic tools (P=0.004 and P=0.001, respectively). CONCLUSION: Intraocular pressure appears to be dependent and positively correlated with CCT changes. However, this does not appear to depend largely on methods used for measuring the CCT in the current study. Corrected intraocular pressure is negatively correlated to both ultrasonically and optically measured central corneal thickness.